Shaping practice from the top down: The impact of federal legislation on ABE practice - Alisa Belzer (Adult Education Research Conference, 2001)
Through case descriptions of twenty-four programs in six states, this study documents the ways in which policy-oriented federal legislation, namely the Workforce Investment Act and Welfare Reform, influences the day to day practices of program administrators and instructors.